Evaluating Career-Development Programs for Women: Critique and Recommendations - Worth Gavin, Darlene A. (Canadian Journal of Counselling and Psychotherapy, 2007)
A descriptive overview of five recently published evaluations of career-development interventions designed specifically for women suggests that these programs need to be more systematically evaluated and reported. Given the limited extent to which existing substantive and methodological knowledge appear to be informing practice, two major strategies are recommended that may be useful to those evaluating future career-development programs for women.